Efektivitas Penggunaan Zoom Dan Google Classroom Sebagai Media Pembelajaran Pada Mata Kuliah Dasar-Dasar Akutansi Semester Ii Tahun Akademik 2021/2022 Universitas Bhinneka PGRI - Khoirina Indrawati; Tutut Suryaningsih (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to determine the effectiveness of the use of Zoom and Google Classroom asLearning Media in the Second Semester Accounting Basics Course in the 2021/2022 Academic Year at the University of Bhinneka PGRI. This research was conducted because technological advances can allow students to do online or online learning by using the Zoom and Google Classroom applications. But in learning to use Zoom and Google Classroom, there are still many obstacles. This research method uses a qualitative approach with a descriptive type. The sampling technique used was purposive sampling technique with the research subject being Lecturer of Accounting Basics Semester II-A and 31 students of Semester II-A Economic Education Study Program. Data collection techniques are carried out through observation, interviews and documentation. Based on the results of the study, it was found that the effectiveness of using Zoom and Google Classroom as learning media in the second semester of accounting basics at the University of Bhinneka PGRI was deemed less effective due to the many obstacles faced in online learning, namely internet limitations and lack of understanding of the material. It is said to be not very effective because it does not include effectiveness points from researchers, namely there is no increase in student learning after learning takes place, when learning is in progress students do not focus on lectures, students do not understand lecture material, lack of student discipline in collecting assignments and poor internet networks good.